OPHTHALMOLOGICAL COMPLICATIONS AFTER LOCO-REGIONAL ANAESTHESIA OF SUPERIOR ALVEOLAR NERVES - LITERATURE REVIEW - Dan Ionuţ Sălăvăstru; Maria Justina Roxana Vîrlan; Victoria Roxana Ivaşcu; Alexandru Poll; Vanda Roxana Nimigean; Ovidiu Muşat; Cătălina Murariu-Măgureanu (Romanian Society of Oral Rehabilitation, 2020)
The superior alveolar nerves ensure the innervation of the maxillary teeth either directly or indirectly, after the formation by anastomoses of the superior dental plexus (the superior alveolar plexus). In dentistry, intraoral loco-regional anaesthesia of these nerves is particularly common, being necessary for various conservative or radical therapeutic procedures at the level of the upper teeth and for dento-alveolar surgical procedures at the maxillary level. During the loco-regional anaesthesia of the superior alveolar nerves, various accidents and complications can occur, some of them being ophthalmological, due to anatomical variations, proximity to the orbital region and sometimes due to technical errors. The present study proposes a review of the recent specialized literature on the occurrence of these ophthalmic complications in order to draw the attention of clinicians to their aetiology and management.